FINANCIAL PERFORMANCE ANALYSIS USING CAMEL METHOD IN PT. BANK SULSELBAR MAKASSAR - Nasrullah, Nasrullah; Ismail, Nur Inayah (Perpustakaan dan Penerbitan Unismuh Makassar, 2018)
This research was conducted at PT.Bank Sulselbar Makassar which is located at JL.Dr.Sam ratulangi No.16 Makassar City.This research aims to determine the performance of financial on PT.Bank Sulselbar Makassar by using CAMEL method (Capital, Asset, Management, Earning, Liquidity) as well as knowing the bank's health level. The type of research used is descriptive quantitative research, data types used are primary and secondary data,the sample used is financial statements for years 2015 , 2016 and 2017. Data collection techniques used are documentation techniques and methods of data analysis is a quantitative descriptive method that is where data are collected, compiled, interpreted, analyzed, classified so as to give information which is complete for problem solvers faced. From the results of financial performance research and kaiitannya with CAMEL method, it can be said for the last three years (2015-2017) which shows that the financial performance achieved by PT.Bank Sulselbar are on a healthy predicate.